سیرت النبی ﷺ اور مستشرقین: Seerah of Prophet Muhammad PBUH and Orientalist - Dr. Abdul Hameed Khan Abbasi; Dr. Tahira Ifraaq (MEI, 2023)
Orientalism and orientalist movement formally emerged as an intellectual warfare against Islam and Muslims in 8th century. The notion based orientalist movement was organized and categorically developed in various stages. The main idea behind this movement was to create doubts in the minds of Muslims about prophet hood of prophet Muhammad (S.A.W) and to halt the propagation of Islam in the world at large. They strategically attack at different facets of the sīrah of prophet Muhammad (S.A.W) by constructing factious stories de facto based on imagination, hatred and prejudice towards Islam. But they set forth baseless arguments in support of their averments which lack coherence, logic and factual proofs. This study proceeds with the introduction about orientalists and orientalism. Different stages of orientalist movement and the political, economic and literary reasons behind it are presented in the following section. The next section of the paper deals with the mistakes and blunders committed by the orientalists in this warfare. The study answers the objections that are raised by the orientalists in the last part.